How far reaches the power of personality? Personality predictors of terminal decline in well-being - Swantje Mueller; Jenny Wagner; Gert G. Wagner; Nilam Ram; Denis Gerstorf (Deutsches Institut für Wirtschaftsforschung (DIW), 2017)
Personality is a powerful predictor of central life outcomes, including subjective well-being. Yet, we still know little about how personality manifests in the very last years of life when well-being typically falls rapidly. Here, we investigate whether the Big Five personality traits buffer (or magnify) terminal decline in well-being beyond and in interaction with functioning in key physical and social domains. We applied growth models to up to 10-year longitudinal data from 629 now deceased participants in the nation-wide German Socio-Economic Panel Study (SOEP; age at death: M = 76 years; SD = 11). Lower neuroticism and higher conscientiousness were each uniquely associated with higher late-life well-being one year prior to death. At the same time, participants low in neuroticism experienced steeper terminal well-being declines. Similarly, individuals high in agreeableness and women high in extraversion reported higher well-being far away from death, but experienced more severe terminal decline, such that personality-related differences in well-being were not discernible anymore at one year prior to death. Interaction effects further revealed that individuals suffering from disability benefit less from higher levels of conscientiousness, while openness to experience appeared particularly beneficial for the less educated. We conclude that in the context of often severe late-life health challenges that accompany the last years of life, adaptive personality-related differences continue to be evident and sizeable for some traits, but appear to diminish and even reverse in direction for other traits. We discuss possible underlying mechanisms and practical implications.
Keywords: 330; terminal decline; well-being; personality; late life; mortality